The Forgotten Radical Peter Maurin : Easy Essays from the Catholic Worker - Maurin, Peter (Catholic practice in North America., 2020)
The definitive edition of Catholic Worker cofounder Peter Maurin's Easy Essays, including 74 previously unpublished works. Although Peter Maurin is well known among people connected to the Catholic Worker movement, his Catholic Worker co-founder and mentee Dorothy Day largely overshadowed him. Maurin was never the charismatic leader that Day was, and some Workers found his idiosyncrasies challenging. Reticent to write or even speak much about his personal life, Maurin preferred to present his beliefs and ideas in the form of Easy Essays, published in the New York Catholic Worker. Featuring 482 of his essays, as well as 87 previously unpublished ones, this text offers a great contribution to the corpus of twentieth-century Catholic life. At first glance, Maurin's Easy Essays appear overly simplistic and preposterous. But upon further investigation, his essays are much more complex and nuanced. Packed with demanding ideas meant to convey dense information and encourage the listener to ponder different ways to understand and interact with reality, his short poetic phrases became his modus operandi for communicating his vision and became a hallmark of his public theology. Each essay contained anywhere from one to ten or more stanzas and were part of a larger arrangement, often titled. Within the larger arrangements were individual essays, which were also titled and arranged in such a manner as to support the overall thesis. Many individual essays were later repeated in slightly altered forms in new arrangements. Previous arrangements were also repeated that omitted or added an essay. Providing scholarly and contextual information for the modern reader, this annotated collection includes more than 350 footnotes which offer a layer of intelligibility that explains Maurin's use of obscure references to historical people and events that would have been common knowledge for readers during the 1930s. When appropriate, the footnotes explain why Maurin chose to cite a person or event. A scholarly Introduction offers a robust synthesis of contemporary scholarship on Maurin and the Catholic Worker that considers radical Catholicism and questions regarding race, ethnicity, religious difference, and gender, because many of Maurin's essays take up these themes. This book shapes the ways Maurin is read in the present day and the ways leftist Catholicism is understood as part of twentieth-century history.